Bromination Improves the Electron Mobility of Tetraazapentacene. Issue 30 (29th June 2018) - Reiss, Hilmar; Ji, Lei; Han, Jie; Koser, Silke; Tverskoy, Olena; Freudenberg, Jan; Hinkel, Felix; Moos, Michael; Friedrich, Alexandra; Krummenacher, Ivo; Lambert, Christoph; Braunschweig, Holger; et al.
Abstract: A cyclocondensation of TIPS‐ethynyl‐substituted diaminoarenes with in situ obtained 4, 5‐dibromocyclohexa‐3, 5‐diene‐1, 2‐dione has led to the synthesis of tetrabromotetraazapentacene (BrTAP). BrTAP is easily reduced to its air‐stable radical anion and electron mobilities >0.56 cm 2 V −1 s −1 can be achieved in thin‐film transistors. Abstract : A fully air‐stable radical anion is formed from a bis‐TIPS‐ethynyl‐substituted tetraazapentacene with four bromine substituents attached in the 2‐, 3‐, 9‐, and 10‐positions. The deep‐lying LUMO (i.e. high electron affinity) makes this material a promising n‐channel semiconductor, as the bromine substituents stabilize charge and lead to a charge distribution that favors the outer rings, which allows better charge transport in the crystalline state.